E-commerce and CSR Strategy: A Comprehensive Analysis - Safari, Ferdi; Mediawati, Noor Fatimah; Masudin, Noor (Proceedings of The ICECRS, 2023)
This data article presents an analysis of scholarly works on E-commerce and CSR Strategy from Lens.org, assessing journal articles for further research. Cardiff University leads with five articles, while Adam Lindgreen is the most prolific author (four articles). Corporate Social Responsibility dominates with 31 articles, primarily from the United Kingdom (33 articles). Springer Nature and the International Journal of Business Ethics are prolific publishers. This dataset aids researchers exploring digital businesses' evolving societal and environmental responsibilities, shaping more responsible corporate strategies. Highlights : Analysis of scholarly works on E-commerce and CSR Strategy from Lens.org. Dominance of Corporate Social Responsibility as a subject. Dataset aiding research on digital businesses' societal responsibilities and strategy design. Keywords: E-commerce, CSR Strategy, Scholarly Works, Data Analysis, Sustainability Research